2019
DOI: 10.3390/molecules24193606
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of pH-Sensitive Tetramycin Releasing Gel and Its Antibacterial Bioactivity against Ralstonia solanacearum

Abstract: Ralstonia solanacearum (R. solanacearum)-induced bacterial wilt of the nightshade family causes a great loss in agricultural production annually. Although there has been some efficient pesticides against R. solanacearum, inaccurate pesticide releasing according to the onset time of bacterial wilt during the use of pesticides still hinders the disease management efficiency. Herein, on the basis of the soil pH change during R. solanacearum growth, and pH sensitivity of the Schiff base structure, a pH-sensitive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Many studies have shown that the sustained release of hydrogel-induced pesticides can remarkably improve the application efficiency of the pesticides. , Ma et al used a Schiff base to crosslink the oxidized alginate and fabricated a pH-sensitive hydrogel that could be used in soil-borne bacterial-derived plant diseases. The Schiff base crosslinking point would be broken under a low pH, and thus the drug loaded in the hydrogel would fastly release into the environment to respond to the growth of the bacteria . A new type of double cross-linked ADH-OSA gel with a pH-dependent pesticide release behavior has high antibacterial activity against Ralstonia solanacearum .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the sustained release of hydrogel-induced pesticides can remarkably improve the application efficiency of the pesticides. , Ma et al used a Schiff base to crosslink the oxidized alginate and fabricated a pH-sensitive hydrogel that could be used in soil-borne bacterial-derived plant diseases. The Schiff base crosslinking point would be broken under a low pH, and thus the drug loaded in the hydrogel would fastly release into the environment to respond to the growth of the bacteria . A new type of double cross-linked ADH-OSA gel with a pH-dependent pesticide release behavior has high antibacterial activity against Ralstonia solanacearum .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The Schiff base crosslinking point would be broken under a low pH, and thus the drug loaded in the hydrogel would fastly release into the environment to respond to the growth of the bacteria. 20 A new type of double cross-linked ADH-OSA gel with a pH-dependent pesticide release behavior has high antibacterial activity against Ralstonia solanacearum. 20 Although the advantage of hydrogels in the application of plant protection has been proved, bulk hydrogels have still not been used to control leaf diseases due to their large size.…”
Section: Introductionmentioning
confidence: 99%
“…50 The composite Pectin/HF-0.5 h showed the highest thermal stability, which could be attributed to the improved interaction fiber/matrix, which helped to delay the thermal decomposition of the pectin. 51,52 In fact, since the mechanochemical treatment removed external non-cellulosic materials, the roughness of treated HF surface tended to increase improving the interconnections between the HF and the polymeric matrix. The onset temperature tended to decrease as the processing time of HF treatment increased.…”
Section: Composites Characterizationmentioning
confidence: 99%
“…Therefore, improving the utilization of pesticides has been a crucial issue over the past decade. Recently, with the rapid development and application of nanotechnology in the agricultural field, a series of environmental-stimulus-responsive pesticide nanosystems [ 5 , 6 , 7 ], such as pH [ 8 , 9 , 10 ], temperature [ 11 , 12 , 13 , 14 ], enzyme [ 15 , 16 , 17 ], redox [ 18 , 19 , 20 ], and light-responsive materials [ 21 , 22 , 23 ], were developed to improve the utilization rate of pesticides and reduce environmental risk. However, to the best of our knowledge, few reports on dual-responsive pesticide delivery nanosystems exist.…”
Section: Introductionmentioning
confidence: 99%